Environmental impact assessment of hemp cultivation and its seed-based food products - Meffo Kemda, Marlyse; Marchi, Michela; Neri, Elena; Marchettini, Nadia; Niccolucci, Valentina (Frontiers in Environmental Science, 2024)
Hemp is a crop cultivated in Europe since ancient times, with a variety of purposes and products. Despite being known for its positive environmental effects on ecosystems, the impacts of hemp-based food products has not been sufficiently investigated yet. This paper contributed to deepen the knowledge of the hemp industry by focusing on the potential environmental impact of the cultivation phase (under three different agronomic practices in Italy: organic and conventional outdoor, and indoor) and the production of selected hemp-based goods (seed oil and flour for food purposes and flowers for therapeutics uses). Impact was quantified utilizing the Life Cycle Assessment within different impact categories Carbon Footprint, Eutrophication, Acidification and Water Footprint. For a carbon offset assessment, the carbon storage capability (i.e. the carbon fixed in crop residues left in the field) of hemp was also investigated through the guidelines provided by the IPCC. The cultivation phase contributed to a CF that ranged from 1.2 (organic outdoor) to 374 (indoor) kg CO2eq for kg of hemp flowers, or 1.9 kg CO2eq per kg of grains (conventional outdoor). These results were in line with literature. Sensitivity scenarios based on hotspot analysis were also presented for CF mitigation for each kind of cultivation. On the other side, the ability of hemp to sequester carbon in the soil due to crop residues left in the field (i.e. carbon storage) was evaluated (-2.7 kg CO2 (ha year) -1 ) showing that the CF was fully compensated (-0.27 kg CO2 (ha year) -1 for conventional outdoor and -1.07 kg CO2 (ha year) -1 for organic outdoor). Regarding hemp-based products, only dried flowers showed a negative balance (-0.99 kg CO2 per kg dry flower), while hemp oil and flour reported positive values (23.41 kg CO2 per kg oil and 31.79 kg CO2 per kg flour), when carbon storage was accounted. The results support the idea that the production chain can be sustainable and carbon-neutral only when all the different parts of the plant (flowers, seeds, fibers, leaves and all residues) were used to manufacture durable goods according to the framework of circular economy.